Productivity, Carcass Traits, and Meat Quality of Local Lambs Fed with Carica pubescens Seeds Meal - Idayanti, R. W.; Istianah, I.; Putri, S. N. H.; Fauziah, A. N.; Murniyadi, Z.; Esnadewi, L. G.; Purbowati, E.; Arifin, M.; Purnomoadi, A. (Faculty of Animal Science, IPB University, 2024)
This study aimed to determine the effect of substituting agricultural by-products of Carica pubescens seeds meal with some concentrates on productivity, carcass characteristics, and meat quality of local lambs. Eighteen male thin-tailed lambs with an average initial body weight of 10.68 ± 1.3 kg (3-4 months old) were treated with a completely randomized design for ten weeks. The feed ingredients were C. pubescens, Pakchong grass (PG), and concentrate (K). Feed ingredients were prepared into complete feed with a balance of forage and concentrate 40:60% with three treatments, namely: T1= 40% PG + 55% K + 5% C. pubescens; T2= 40% PG + 47.5% K + 12.5% C. pubescens; and T3= 40% RG + 40% K + 20% C. pubescens. The use of 20% C. pubescens-treated lambs was statistically different (p<0.05) regarding the increasing BWG (115.60 g/day), CPI (104.96 g/day), FCR (6.40), slaughter weight (19.62 kg), carcass weight (7.83 kg), meat weight (4.49 kg), and fat weight (1.66 kg). The treatment with 12.5% C. pubescens resulted in significantly different increasing tenderness (p<0.05) in longissimus dorsi and biceps femoris muscle pain (2.79 kgf/cm2) and (3.36 kgf/cm2), respectively. The inclusion level of C. pubescens seeds up 20% resulted in higher body weight gain, crude protein intake, feed cost ratio, slaughter weight, carcass weight, and meat weight.